Comparison of Laparoscopy and Laparotomy for Para-Aortic Lymphadenectomy in Women With Presumed Stage I–II High-Risk Endometrial Cancer - Paik, E Sun; Baek, Seung Hun; Kang, Jun Hyeok; Jeong, Soo Young; Kim, Myeong Seon; Kim, Woo Young; Lee, Yoo-Young; Choi, Chel Hun; Lee, Jeong-Won; Kim, Byoung-Gie; Bae, Duk-Soo; Kim, Tae-Joong (Frontiers in Oncology, 2020)
Objective: To compare laparoscopic surgery to laparotomy for harvesting para-aortic lymph nodes in presumed stage I-II, high-risk endometrial cancer patients. Methods: Patients with histologically proven endometrial cancer, presumed stage I-II with high-risk tumor features who had undergone hysterectomy, bilateral salpingoophorectomy, or pelvic and para-aortic lymphadenectomy by either laparoscopy or laparotomy in Samsung Medical Center from 2005 to 2017 were retrospectively investigated. The primary outcome was para-aortic lymph node count. Secondary outcomes were pelvic lymph node count, perioperative events, and postoperative complications. Results: A total of 90 patients was included (35 for laparotomy, 55 for laparoscopy) for analysis. The mean (+/-SD) para-aortic lymph node count was 10.66 (+/-7.596) for laparotomy and 10.35 (+/-5.848) for laparoscopy (p=0.827). Mean pelvic node count was 16.8 (+/-6.310) in the laparotomy group and 16.13 (+/-7.626) in the laparoscopy group (p=0.664). Lower estimated blood loss was shown in the laparoscopy group. There was no difference in perioperative outcome between the groups. Additional multivariate analysis showed that survival outcome was not affected by surgical methods in presumed stage I-II, high-risk endometrial cancer patients. Conclusions: Study results demonstrate comparable para-aortic lymph node count with less blood loss in laparoscopy over laparotomy. In women with presumed stage I-II, high-risk endometrial cancer, laparoscopy is a valid treatment modality.